Financial conflicts of interest of clinicians making submissions to the pan-Canadian Oncology Drug Review: a descriptive study - Joel Lexchin (BMJ Open)
Objectives This study examines financial conflict of interest (FCOI) of clinicians who made submissions to the pan-Canadian Oncology Drug Review (pCODR), the arm of the Canadian Agency for Drugs and Technology in Health that recommends whether oncology drug indications should be publicly funded. Final reports from pCODR published between October 2016 and February 2019 were examined.Design Descriptive study.Data sources Website of pCODR.Interventions None.Primary and secondary outcomes The primary outcome is the number of submissions declaring FCOI. Secondary outcomes are the number of times where clinicians agreed and disagreed with preliminary recommendation from pCODR and the association between the distribution of individual clinicians’ FCOI and pCODR’s funding recommendations.Results There were 46 drug indication reports from pCODR. Clinicians made 261 submissions. Clinicians declared they received payments from companies 323 times and named 38 different companies making those payments a total of 500 times. Financial conflicts with drug companies were declared in 176 (66.3%) of all submissions. In 21 (45.7%) of the 46 drug indications, 50% or more of the clinicians had a conflict with the company making the drug. Clinicians commented on 37 preliminary recommendations. In all 25 where pCODR recommended funding or conditional funding, the clinicians either agreed or agreed in part. pCODR recommended that the drug indication not be funded 12 times and 9 times clinicians disagreed with that recommendation. The distribution of clinician responses was statistically significantly different depending on whether pCODR recommended funding/conditional funding or do not fund p<0.0001 (Fisher exact test). The distribution of clinicians’ FCOI differed depending on whether the recommendation was fund/conditional fund or do not fund p=0.027 (Fisher exact test).Conclusion Financial conflicts with pharmaceutical companies are widespread among experts making submissions to the pCODR.